2020
DOI: 10.2147/dddt.s276005
|View full text |Cite
|
Sign up to set email alerts
|

<p>Activation of PI3K/Akt/HIF-1α Signaling is Involved in Lung Protection of Dexmedetomidine in Patients Undergoing Video-Assisted Thoracoscopic Surgery: A Pilot Study</p>

Abstract: Background: Lung resection and one lung ventilation (OLV) during video-assisted thoracoscopic surgery (VATS) may lead to acute lung injury. Dexmedetomidine (DEX), a highly selective α 2 adrenergic receptor agonist, improves arterial oxygenation in adult patients undergoing thoracic surgery. The aim of this pilot study was to explore possible mechanism related to lung protection of DEX in patients undergoing VATS. Patients and Methods: Seventy-four patients scheduled for VATS were enrolled in this study. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…This pathway is closely related to neuronal survival because many neurotrophic factors play a protective role in the brain by activating the pathway, thus inhibiting apoptosis [ 22 ]. Similar to our findings, a previous study showed that dexmedetomidine improved propofol-induced neuronal injury in rat hippocampus through the PI3K/Akt pathway [ 23 ]. Also, this pathway had protective effects of propofol on intestinal and lung injury induced by intestinal ischemia [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…This pathway is closely related to neuronal survival because many neurotrophic factors play a protective role in the brain by activating the pathway, thus inhibiting apoptosis [ 22 ]. Similar to our findings, a previous study showed that dexmedetomidine improved propofol-induced neuronal injury in rat hippocampus through the PI3K/Akt pathway [ 23 ]. Also, this pathway had protective effects of propofol on intestinal and lung injury induced by intestinal ischemia [ 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Of the 1218 potential articles in the initial search, 20 RCTs 24–43 met the inclusion criteria. The screening and selection process is demonstrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, the processes of randomization, allocation concealment and blinding were inadequate in these studies, 29–35,38–43 which indeed would cause selection bias and diagnostic bias.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with these findings, the present data indicated that LY294002 pretreatment markedly abolished the protective effects of DEX on LPS-induced lung inflammation, oxidative stress, and apoptosis in mice. Several studies demonstrated that pretreatment with DEX ameliorated LPS-induced acute lung injury [ 40 – 42 ], and DEX was also reported to alleviate lung ischemia–reperfusion-induced acute lung injury [ 43 ], and to alleviate lung ventilation (OLV) during video-assisted thoracoscopic surgery (VATS) lead to acute lung injury partly through activating PI3K/Akt signaling pathway [ 44 ]. However, unknown are whether DEX ameliorates LPS-induced lung inflammation, oxidative stress, and apoptosis and whether the protective effect of DEX involves the PI3K/Akt/FoxO1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%